MENGKAJI KEUNGGULAN KURIKULUM IPA FINLANDIA UNTUK MENINGKATKAN PENDIDIKAN SAINS DI INDONESIA - Nasution, Asrin Asrin (NIZHAMIYAH, 2024)
The issues in education in Indonesia, particularly in the field of Natural Sciences, are very concerning. According to the Programme for International Student Assessment (PISA) survey by the OECD, Indonesian students' abilities in science rank low globally, with a ranking of 71 out of 77 countries in 2018 and 68 out of 81 countries in 2023. The science scores also declined from 396 to 383, far below the RPJMN target of 402. Data from the Trends in International Mathematics and Science Study (TIMSS) shows that Indonesian 4th and 8th-grade students also rank low internationally. The research methodology uses a qualitative approach through a literature study. Data analysis indicates that the content and competency-based science curriculum in Finland provides a good model by integrating theoretical knowledge and practical skills. Science education in Finland, which is interactive and student-centered, can serve as a reference for improving the curriculum in Indonesia. A comprehensive and context-based science learning approach is needed to enhance the quality of science education in Indonesia. The PISA and TIMSS survey results emphasize the need for improvements in science learning in Indonesia. Science, as systematic knowledge and a scientific process, requires a holistic and integrated learning approach. An integrated science approach that connects science to everyday life is crucial for developing scientific processes in students. Science teachers are expected to have interdisciplinary abilities and knowledge integration. However, often the curriculum and the quality of teachers do not support this goal. This study compares the 2013 Curriculum in Indonesia with the Finnish Curriculum to see the similarities, differences, and obstacles in science learning.